Integrating Cultural Competency Throughout a First-Year Physician Assistant Curriculum Steadily Improves Cultural Awareness. - Beck, Barbra; Scheel, Matthew H.; De Oliveira, Kathleen; Hopp, Jane (Journal of Physician Assistant Education (Physician Assistant Education Association), 2013)
Purpose: this study tracked student self-assessments of cultural awareness at regular intervals during the first year of a master's of science physician assistant (PA) program to test effectiveness of a cultural competency component in the curriculum. Method: Students completed a cultural awareness survey at the beginning of the program and retook the survey at approximately 4-month intervals throughout the first year. Results: Regression analyses confirmed positive linear relationships between survey number and score on 31 of 31 items. Conclusion: Cultural awareness among PA students benefits from repeated exposures to lessons on cultural competency. Schools attempting to develop or expand cultural awareness among students should consider presenting material in multiple courses across terms.